The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1526-100x.1994.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of a Relocated Population of Endangered Iguana pinguis on Guana Island, British Virgin Islands

Abstract: Eight individual rock iguanas (Iguana pinguis) from Anegada Island were relocated to Guana Island by Lazell, 1984–1987, in order to establish a second population reservoir for this endangered species. The species may have originally occupied the entire Puerto Rico Bank. The relocation has been successful and, in the area currently providing the best habitat, we estimate a density of 9 or 12 animals of various age classes per 19 ha. The optimal area contains a sheep exclosure with relatively dense understory ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…Past studies of Cyclura populations have reported home-range sizes varying by one order of magnitude among individuals (Carey, 1975;Iverson, 1979;Goodyear and Lazell, 1994;Mitchell, 1999;Knapp, 2000), rather than the two orders of magnitude reported here. Our minimum overall home-range sizes for iguanas are not attributable to inadequate sampling as the two smallest home ranges for 2002 (100% MCPs with all data of , 0.7 ha; both females) were based on 273 and 327 locations collected over a 185-day period, which are large sample sizes compared to most studies in Cyclura.…”
Section: Discussionmentioning
confidence: 55%
“…Past studies of Cyclura populations have reported home-range sizes varying by one order of magnitude among individuals (Carey, 1975;Iverson, 1979;Goodyear and Lazell, 1994;Mitchell, 1999;Knapp, 2000), rather than the two orders of magnitude reported here. Our minimum overall home-range sizes for iguanas are not attributable to inadequate sampling as the two smallest home ranges for 2002 (100% MCPs with all data of , 0.7 ha; both females) were based on 273 and 327 locations collected over a 185-day period, which are large sample sizes compared to most studies in Cyclura.…”
Section: Discussionmentioning
confidence: 55%
“…Among iguanid lizards, males typically have larger home ranges than females (reviewed in Perry and Garland, 2002), and this is true of most species of Cyclura that have been studied (Carey, 1975;Iverson, 1979;Goodyear and Lazell, 1994;Mitchell, 1999;Knapp, 2000; but see Alberts et al, 2002). Similarly, male C. lewisi in this study had larger home ranges than females during the entire study period.…”
Section: Discussionmentioning
confidence: 59%
“…This study represents the longest telemetry investigation on a natural Cyclura population in the West Indies. The relatively few studies that have attempted to estimate Cyclura home ranges were hampered with transmitter attachment failures and thus occurred only over limited time periods ranging from days to ≈ 4 weeks (Wiewandt, 1977;Iverson, 1979;Goodyear & Lazell, 1994;Mitchell, 1999;Hayes et al, 2004). Accurate estimates should improve in the future as attachment technologies are refined and tested.…”
Section: Home Rangementioning
confidence: 99%
“…Home-range estimates for the Andros iguana are considerably larger than previously published for natural populations of West Indian iguanas. An inadequate number of re-location sightings via telemetry are most probably responsible for the low estimates on some islands (see Carey, 1975;Wiewandt, 1977;Goodyear & Lazell, 1994;Mitchell, 1999), or for other estimates this phenomenon is probably an artifact of island size and population density (see Knapp, 2000;Hayes et al, 2004). West Indian iguanas inhabit islands ranging from < 1 ha cays in the Bahamian Archipelago to the > 110 000 km 2 landmass of Cuba.…”
Section: Home Rangementioning
confidence: 99%